2017
DOI: 10.1002/pro.3233
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional diversity of EF‐hand proteins: Evolutionary perspectives

Abstract: We have classified 865 sequences of EF-hand proteins from five proteomes into 156 subfamilies. These subfamilies were put into six groups. Evolutionary relationships among subfamilies and groups were analyzed from the inferred ancestral sequence for each subfamily. CTER, CPV, and PEF groups arose from a common EF-lobe (pair of adjacent EF-hands). They have two or more EF-lobes; the relative positions of their EF-lobes differ from each other. Comparisons of the ancestral sequences and the inferred structures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 47 publications
0
61
0
Order By: Relevance
“…PAP1‐a was a heterodimer formed by the association of S100A1‐α and S100B‐β subunits, whereas PAP1‐b was a homodimer of two S100B‐β subunits. Chemical sequencing of the S100A1‐α and S100B‐β subunits showed that they were members of the EF‐hand calcium‐binding superfamily of proteins that includes calmodulin, troponin C and parvalbumin (Isobe & Okuyama, , ); (Kawasaki & Kretsinger, ). Studies on the physico‐chemical and structural properties of the brain homodimers S100A1 and S100B and of the heterodimer S100A1/S100B confirmed Ca 2+ binding and revealed specific high‐affinity binding of Zn 2+ by the S100B protein (Baudier & Gerard, , ; Baudier et al ., ; Baudier, Labourdette & Gerard, ; Baudier, Glasser & Gerard, ).…”
Section: Introductionmentioning
confidence: 99%
“…PAP1‐a was a heterodimer formed by the association of S100A1‐α and S100B‐β subunits, whereas PAP1‐b was a homodimer of two S100B‐β subunits. Chemical sequencing of the S100A1‐α and S100B‐β subunits showed that they were members of the EF‐hand calcium‐binding superfamily of proteins that includes calmodulin, troponin C and parvalbumin (Isobe & Okuyama, , ); (Kawasaki & Kretsinger, ). Studies on the physico‐chemical and structural properties of the brain homodimers S100A1 and S100B and of the heterodimer S100A1/S100B confirmed Ca 2+ binding and revealed specific high‐affinity binding of Zn 2+ by the S100B protein (Baudier & Gerard, , ; Baudier et al ., ; Baudier, Labourdette & Gerard, ; Baudier, Glasser & Gerard, ).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the M48K mutation does not affect the expression of FKBP22 in the rER but leads to an FKBP22 with weakened functions. Here we show that a partial loss of function leads to a similar phenotype as the complete loss of FKBP22 even though M48K FKBP22 could still have fully functional EF hand motifs, the function of which is mostly unknown except for binding calcium 30,31 . The molecular findings are in keeping with the clinical findings of the homozygous M48K patient which were similar to these of FKBP22 null patients 7 .…”
Section: Scientific Reports |mentioning
confidence: 83%
“…In particular, ICAP2 is nearly twice as long as its mammalian counterparts and appears to have an EF-like domain in its N terminus. EF domains bind cations like Ca 2+ or Mg 2+ and can act to modulate protein-protein interactions or enzymatic activity (Kawasaki & Kretsinger, 2017). The mitochondrial matrix is known to act as a Ca 2+ store, and the presence of an EF-like domain suggests that ATP synthase activity may be somehow coordinated with mitochondrial Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%